Single cell whole genome amplification in optofluidic platform and sequencing assessment from the Biology and Mars Experiment (BIOMEX) - Liu, Y.; Jeraldo, P.; Schulze-Makuch, D.; de Vera, Jean Pierre Paul; Cockell, C.; Leya, Thomas; Baque, Mickael; Walther-Antonio, M. (2019)
Genome sequencing of single microbial cells in low biomass settings such as in extreme conditions could lead to crucial findings in astrobiological pursuits. Typically, sequencing requires high biomass and averages over genomically heterogeneous populations, concealing the valuable information hidden within very few cells. Single cell whole genome sequencing is capable of identifying microbes with low representation which is often neglected or undetectable in traditional studies. It can also detect rare mutation events in single cells, which allows for mutagenic and detailed evolutionary work. In this work, we use an optofluidic platform that integrates advanced microscopy, laser tweezers and microfluidic technology to isolate single cells of Gleocapsa sp., Sphaerocystis sp. Arctic strain CCCryo 101-99 and Nostoc sp. Antarctic strain CCCryo 231-06 for whole genome amplification and sequencing to identify the genomic variation among the cells exposed to different conditions, including the ground controls (Earth), Mars simulator on Earth, and the simulated Martian condition on the International Space Station. This work presents an unparalleled study of single cell mutagenic events within a population and observation of the raw rate of mutation events that a single cell experiences under these conditions and shed light on microbial responses to space radiation.